The Effect of Digital Learning Adoption, Self-Regulated Learning, and Learning Engagement on Students’ Learning Outcomes - Pietra Dorand; Netti Zurnelli; Sally Putri Karisma; Muhammad Arsyad (Journal Management & Economics Review (JUMPER), 2026)
This study examines the effect of digital learning adoption, self-regulated learning, and learning engagement on students’ learning outcomes in technology-enhanced educational environments. Using a quantitative explanatory research design, data were collected from 268 undergraduate students who had experienced online or blended learning. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among the variables. The results indicate that digital learning adoption has a significant positive effect on students’ learning outcomes. Additionally, self-regulated learning and learning engagement both significantly influence learning outcomes, with learning engagement emerging as the strongest predictor. The findings further reveal that digital learning adoption significantly enhances students’ self-regulated learning and engagement, which in turn mediate its impact on academic performance. The model explains 68.2% of the variance in learning outcomes, demonstrating strong predictive power. These results suggest that the effectiveness of digital learning depends not only on technological implementation but also on students’ ability to regulate their learning and actively engage in academic activities. The study highlights the importance of integrating digital infrastructure with pedagogical strategies that foster autonomy and engagement to optimize students’ academic success in digital learning environments.